Obesity prevalence, physical activity, and dietary practices among adults in Saudi Arabia - Alsulami, Salhah; Baig, Mukhtiar; Ahmad, Tauseef; Althagafi, Nouf; Hazzazi, Eman; Alsayed, Razan; Alghamdi, Majd; Almohammadi, Thikra (Frontiers in Public Health, 2023)
Introduction The current study evaluated obesity prevalence, physical activity, and dietary practices among Saudi adults in the Makkah region of the Kingdom of Saudi Arabia (KSA). The current survey was accomplished between November 2021 and March 2022. Method A validated questionnaire, Arab Teens Lifestyle Study (ATLS), was used to evaluate all participants' physical activities, sedentary behaviors, and nutritional habits in addition to demographic data. Result A total of 2,115 people [1,238 (58.5%) women and 877 (41.5%) men] participated in this survey. Being overweight was prevalent in 32.8% of the population (41% of men and 28.9% of women), obesity was prevalent in 23% of the population (males 23.1% and females 24.2%). Obese people consumed more soft drinks, and overweight people did not consume enough vegetables (fresh/cooked). Obese people consumed fast food (e.g., burgers, sausage, pizza, or Arabic shawarma) over three times each week. The mean (SD) number of days of practice walking was 2.51 (2.05) vs. 1.3 (1.87) (p < 0.001) for lean and obese individuals, respectively. In addition, individuals with normal BMI had more days of jogging, moderate and high-intensity exercise, dancing, and strength training than those with obesity. The odds of being obese increased with age (OR: 1.07; p < 0.001), in males (OR: 2.16; p < 0.001), in participants earning <5,000 SR/month (1.3 thousand $) and 10–15 thousand SR/month (1.34–2.66 thousand $) (OR: 2.36; P = 0.01). Obesity was inversely associated with moderate-intensity exercise (OR: 0.802; p = 0.009), and regular walking (OR: 0.685; CI: 0.624–0.752; p < 0.001). Discussion Overweight and obesity were prevalent in 32.8% and 23% of the population, respectively. Sociodemographic factors associated with obesity. Focused intervention strategies are needed to overcome the obesity issue.